Integrating Grammar and communication in English lessons (Eurasian Journal of Humanities and Social Sciences, 2025)
Grammar and communication are two essential components of English language teaching, yet they have often been treated as separate entities in traditional classrooms. This article explores the importance of integrating grammatical instruction with communicative practice to develop both accuracy and fluency among English learners. Drawing from recent pedagogical theories and classroom research, it argues that communicative competence depends not only on understanding grammatical rules but also on the ability to apply them meaningfully in authentic contexts. The study reviews theoretical perspectives such as Krashen’s Input Hypothesis, Swain’s Output Hypothesis, and Long’s Interaction Hypothesis to demonstrate how grammar and communication intersect in language acquisition. Furthermore, the article provides practical classroom approaches- task-based learning, contextualized grammar teaching, and focus on form designed to help teachers maintain a balance between structure and communication. Challenges faced by teachers and learners are discussed, along with recommendations for curriculum development and teacher training. The paper concludes that an integrated approach enables learners to internalize grammatical forms naturally while developing confidence and competence in real-world communication.